STEM build program: An initiative towards promoting students thinking and communicative skills - Abd Rauf, Rose Amnah; Sathasivam, Renuka V.; Abdul Rahim, Suzieleez Syrene; Rasul, Mohamad Sattar (2018)
The goal of STEM education is to provide students with skills necessary for success in today's workforce. These skills are defined as real world problem solving inquiry, and creative and critical thinking. This can be achieved by moving towards student-centered teaching. This paper will describe a STEM intervention Program for 60 primary school students which employed an engineering design process as its instructional design. This paper will also discuss on the outcome of the program on the student thinking and communicative skills. Students were engaged in designing a prototype to solve a world challenge by applying science and mathematics concept in the project. The process of designing the prototype was found able to give autonomy to the students to think, plan create and test their ideas and improve on it. During the process their thinking skills and communicative skills were put into practice. Teachers were given training on how to execute this program which secs them a the facilitator and students as the active learner. The advantage of this program is that it provide students with informal practice creatively solving problems long before they need to decide on a course of study for college. The opportunity to practice and understand engineering skill open up a world of possibilities for the students to experience and gained knowledge as to what their careers may be like. Using engineering design principles to complete hands-on, problem-based projects also deepens the student's understanding of scientific processes and emphasize on the 21st Century Skill.